Variation of ABA and carotenoids during flowering initiation in carrots - Samuolienė, Giedrė; Duchovskis, Povilas (Acta Biologica Szegediensis, 2006)
The aim - to investigate the dynamics and interaction of abscisic acid and carotenoids in carrot during different flowering initiation stages. The process of carrot flowering initiation and morphogenesis was studied in a phytotron facility: EXP1 – photoperiod of 0 h and 4°C temperature, EXP2 – photoperiod of 8 h and 4°C temperature, EXP3 – photoperiod of 16 h and 4°C temperature, EXP4 – photoperiod of 8 h and 21/16°C temperature, EXP5 – photoperiod of 16 h and 21/16°C (day/night) temperature. High-performance liquid chromatography (HPLC) with diode array detector was used for separation and determination of phytohormones (cytokinin, gibberellic acid, indol-3-acetic acid, and abscisic acid). Spectrofotometric analysis of total carotenoids quantification was made by 644 nm spectrophotometer. The development of carrots with 9 leaves in rosette in different treatments was not identical. Carrots grown in higher temperatures contained a higher level of carotenes in roots than did carrots grown in lower temperatures. Thought such tendencies were not observed in carrot leaves. During flower initiation stage the increase of ABA level in leaves and the decrease in roots was observed in all treatments. The common tendency of carotenoid content variation was observed under treatment with low temperatures and short day photoperiod. These changes can be connected with plant preparation for flowering and seed formation. To summarize, low positive temperatures and short day photoperiod conditioned the most rapid formation of elements of inflorescence axis and the fast growth of generative organs. Also these conditions determined low ABA levels in carrot leaves. Temperature makes the highest effect on carotenoid synthesis in carrot root although in leaves this effect is suppressed by short day photoperiod.